The Influence of Transformational Leadership Style and Work Discipline on Teacher Performance: Work Motivation as an Intervening Variable (Case Study on TK-SD MKD) - Heny Desi Soviana; Veithzal Rivai Zainal; Setyo Riyanto (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
With work motivation as an intermediary variable, this study aims to investigate the impact of transformational leadership styles and work discipline on educator productivity. The aim of the mixed methods sequential explanatory design of the study was to provide a qualitative explanation for the findings of the initial (quantitative) study. To collect information, 36 educators in TK-SD MKD were given questionnaires, and 3 (three) research subjects were interviewed. Structural Equation Model-Partial Least Square (SEM-PLS) and in-depth interviews of each subject were used for quantitative and qualitative data analysis. Transformational leadership style was found to have a positive effect and was significantly related to work motivation, work discipline was found to have a positive effect and was significantly related to work motivation, work discipline was found to have a positive effect and was significantly related to teacher performance, work motivation was found to have a positive effect and was significantly related to teacher performance, style transformational leadership was found to have a positive effect and was significantly related to teacher performance through work motivation, and work discipline was found to have a positive effect and was significantly related to teacher performance through work motivation. However, research has found that transformational leadership style has no effect on teacher performance